Analysis of centrosomes in human cancer - Duensing, Stefan (Centrosome & centriole, 2015)
Centrosomes are small cytoplasmic organelles that function as major microtubule-organizing centres during interphase and mitosis. In cancer cells, centrosomes are frequently abnormal in number, size, and structure. Numerous studies have reported centrosome aberrations in human tumors where they frequently increase with malignant progression and advanced disease stage. However, there are a number of caveats when analyzing centrosomes in human tissue. Besides the actual immunodetection and quantification of centrosomes, which can be difficult and cumbersome, centrosome aberrations require a careful evaluation in the cellular context in which they occur. This chapter highlights the importance of careful interpretation of centrosome aberrations in human tumors.
Gesehen am 02.07.2020